Directed abstraction during initial skill learning promotes performance and lasting self-concept change. - Zunick, Peter V.; Fazio, Russell H. (Self & Identity, 2020)
Learning a new skill is often characterized by discouraging setbacks. We administered a directed abstraction writing exercise to encourage participants struggling to learn a programming language (over three weekly sessions) to generalize broadly from their successes. This intervention produced benefits for certain subsets of participants, including those who initially struggled to learn, believed their abilities were changeable, and had negative initial self-concepts regarding computers and programming. The benefits of directed abstraction included more positive self-concepts, motivation, and even performance one month following the final learning session. These results expand on past findings, showing benefits of directed abstraction over time and in a realistic learning setting, while further exploring for whom directed abstraction has the greatest benefits.